2021
DOI: 10.3389/fnmol.2021.697440
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 Receptor Agonist Ameliorates 1-Methyl-4-Phenyl-1,2,3,6-Tetrahydropyridine (MPTP) Neurotoxicity Through Enhancing Mitophagy Flux and Reducing α-Synuclein and Oxidative Stress

Abstract: Parkinson disease (PD) is the second most common neurodegenerative disease without known disease modification therapy to slow down disease progression. This disease has pathological features of Lewy bodies with α-synuclein aggregation being the major component and selective dopaminergic neuronal loss over the substantia nigra. Although the exact etiology is still unknown, mitochondrial dysfunction has been shown to be central in PD pathophysiology. Type 2 diabetes mellitus has recently been connected to PD, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 67 publications
(84 reference statements)
4
22
0
1
Order By: Relevance
“…In this disease, antioxidants were found to decrease ROS levels and their harmful consequences [ 48 ]. Later, when investigating the neuroprotective effects of GLP-1R agonists on PD, researchers found that this is related to its function of antioxidative stress and reduction of mitochondrial dysfunction [ 7 , 23 ]. Consistent with this, our work demonstrates that both semaglutide and liraglutide can reduce ROS levels and increase mitochondrial membrane potential in SH-SY5Y cells exposed to 6-OHDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this disease, antioxidants were found to decrease ROS levels and their harmful consequences [ 48 ]. Later, when investigating the neuroprotective effects of GLP-1R agonists on PD, researchers found that this is related to its function of antioxidative stress and reduction of mitochondrial dysfunction [ 7 , 23 ]. Consistent with this, our work demonstrates that both semaglutide and liraglutide can reduce ROS levels and increase mitochondrial membrane potential in SH-SY5Y cells exposed to 6-OHDA.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that raising autophagy critically allows the GLP-1 analog to exert a wide range of effects, including neuroprotection [ 20 , 21 ]. In addition, through continuous research, oxidative stress and mitochondrial dysfunction were found to be involved in the pathogenesis of PD by mediating apoptosis [ 22 , 23 ]. Therefore, we suggest that the enhancement of autophagy and antioxidative stress, together with a reduction in mitochondrial dysfunction, are pivotal molecular mechanisms underlying the beneficial outcomes of semaglutide against 6-OHDA-mediated toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…The other oral hypoglycemics, DPP-4 inhibitors (or gliptins) can enhance the bioavailability of GLP-1 for the purpose of increasing incretin levels. For example, the DPP4 inhibitor sitagliptin could ameliorate rotenone-induced decrease of dopamine production and improve motor function in a rotenone PD rat model, as discussed above [ 137 ]. Supporting this, treatment with DPP4 inhibitors confer beneficial effects on the baseline nigrostriatal dopamine degeneration and long-term motor outcomes in diabetic patients with PD and may extend its role into non-diabetic patients with PD [ 138 ].…”
Section: The Linkage Between Dm and Pdmentioning
confidence: 99%
“…Aberrant mitochondrial accumulation occurs in neuronal autophagosomes of PD patients [ 19 21 ]. Defective mitophagy flux and mitochondrial damage have also been demonstrated in PD models in vivo and in vitro [ 22 , 23 ]. Therefore, enhancing mitophagy may be a potential strategy for the treatment of PD [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%